PERAN PEMBINA PRAMUKA DALAM MENERAPKAN PERILAKU PROSOSIAL SISWA KELAS X SMA NEGERI 1 JAWAI - Nurdiansyah, Nurdiansyah; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ The purpose of this study is to describe the role of the Scoutmaster in applying the aspects of Prosocial Behavior for Grade X Students of SMA Negeri 1 Jawai, Sambas Regency. This researcher was conducted with a descriptive research method using a qualitative form. The research techniques used are 1. Direct Communication Techniques and 2. Observation Study Techniques. From the results of this study can be concluded as follows: 1) The role of scoutmaster in implementing sharing behavior in class X students of SMA Negeri 1 Jawai Sambas Regency, plays a very good role. 2.) The role of the scoutmaster in implementing cooperation in class X students of SMA Negeri 1 Jawai Sambas Regency, played a fairly good role. 3) The role of the scout coaches in implementing the behavior of helping to help class X students of SMA Negeri 1 Jawai Sambas Regency, this can be seen from the activities that he fostered, where the scoutmaster always reminds scout members to share and help people who are in pain or disasters, because the scoutmaster said as a scout's soul.Â Keyword : The Role of Scoutmaster, Prosocial Behavior, High School Students.